Accelerating Preferences: Understanding the Impact of Product Variation, Design, And Innovation on Honda Brio Car Purchases In Pekanbaru City - hari wardana; Ferizal Rachmad (Institut Riset dan Publikasi Asas Nusantara., 2023)
This study aims to identify the effect of Product Variation, Product Design, and Product Innovation on consumer purchasing decisions for Honda Brio cars in Pekanbaru City. The research method used is qualitative by using a questionnaire instrument as a means of collecting data from all Pekanbaru City people who use or buy Honda Brio cars. Sampling was done by purposive sampling method. The collected data were analyzed using SPSS version 26 with multiple linear regression analysis. The results of the research show that Product Variation, Product Design, and Product Innovation have a significant and positive influence on consumer purchasing decisions. The implication of this research is the need to continue to innovate and pay attention to product variability and attractive designs to increase consumer attractiveness and achieve competitive advantage in the automotive industry.